UNPLANNED, URGENT AND EMERGENCY CARE: WHAT ARE THE ROLES EMS PROVIDE FOR OLDER PEOPLE WITH DEMENTIA? A LITERATURE REVIEW AND NARRATIVE SYNTHESIS. Issue 5 (18th April 2015) - Buswell, Marina; Martin, Steven; Lee, Caroline; Lumbard, Phillip; Prothero, Larissa
Abstract : Background: Anecdotally emergency ambulance crews say they frequently encounter older people with dementia (OPWD) and it can be difficult to take history, assess pain and access suitable alternatives to the emergency department especially out of hours. With the current policy landscape of the NHS England Emergency & Urgent Care Review and the high profile of dementia care it is pertinent to ask what role emergency medical services (EMS) have in the urgent and emergency care of OPWD. Methods: Aware that the research literature in this area was likely to be sparse we used systematic and iterative search techniques to identify relevant studies and documents. All databases available via NHS Evidence were searched and grey literature was included. Articles which made any reference to the pre-hospital role of EMS ambulance services/personnel in the urgent or emergency care of OPWD were included. Discharge roles were excluded. Results: Nineteen relevant documents were included for review and synthesis, over half from the grey literature. Eight were specifically about EMS treating OPWD, six of those from the grey literature. The other documents, though mentioning the role, were not researching or evaluating that role. We identified three roles described in the literature; emergency transport, assess and manage, and a last resort/safety net role. This final role is alluded to in over one third of the documents but is not investigated. Conclusions and recommendations: This review highlights a gap in our understanding and in the research literature about the role EMS play in the care of OPWD, particularly around the last resort/safety net role. We hope it will encourage researchers from EMS and dementia care disciplines to come together, particularly to look at: ▸ Better understanding the last resort/safety net role. ▸ Evaluating AND reporting in the research literature initiatives that are happening in EMS around caring for OPWD.